PERAN HUKUM ISLAM DALAM MENJAGA ETIKA BISINIS DI ERA EKONOMI BERKELANJUTAN - Muhammad Alif; Muhammad Zidane; Hanif Yasir (Taksasila Edukasi Insani, 2025)
The development of the world economy is increasingly dependent on the urgent application of the principle of sustainability in business activities. Amidst the complexity of economic, social, and environmental issues, ethics plays a crucial role in shaping a just and responsible economic order. Sharia law provides comprehensive normative guidance based on spiritual and moral values aligned with the principles of sustainable development. This study looks at how Islamic law upholds moral business practices in a long-term economy. This study concludes that Islamic legal principles, such as honesty (ṣidq), justice ('adl), and trustworthiness, along with prohibitions against usury, gharar, and fraud, will likely influence ethical business conduct. It does this by using normative legal research methods and a qualitative approach to primary sources, such as the Qur'an and Hadith, as well as literature on Islamic economics and ethics. Through systems like zakat and waqf, these ideals promote environmental sustainability, public welfare, and equitable distribution of wealth.Keywords: Islamic law, business ethics, sustainable economies, sharia, and moral responsibility.